ILOCUTION SPEAKING IN LANGUAGE INTERACTION OF SANTRI AT PONDOK PESANTREN NURUL ILMI WAL FIKRI JOMBANG - Abdur Rahman Haidar (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
When the students interact, there is what is called a speech act or language interaction which includes speakers and opposing speakers, both individually and in groups. When interacting, there will be the application of language acts responsively to their fellow scopes, as well as actions in the form of verbal and behavioral. A speaker performs speech acts well because they are used to their environment. As in the santri at the Nurul Ilmi Wal Fikri Jombang Islamic boarding school, for survival in the pesantren the santri interact and there must be a purpose and application or purpose of the interaction. In the application of communication, the researchers observed the students with the illocutionary phenomenon. There are three illocutions contained in this study, namely; directive illocutionary, expressive illocutionary, and commissive illocutionary. This study uses a descriptive qualitative method, with data collection techniques in the form of observation, note taking, and documentation. Data validity techniques include; data transcription, understanding data, verifying data, modifying data and analyzing data. The results of this study are the students at the Nurul Ilmi wal fikri Jombang Islamic boarding school when interacting there will definitely be an application and purpose in communication, which can be verbal or behavioral.